2013
DOI: 10.1177/0884533613506596
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Parenteral Nutrition

Abstract: Parenteral nutrition (PN) is a life-sustaining therapy for hundreds of thousands of people who have severe impairment of gastrointestinal function. Trace elements are a small but very important part of PN that can be overlooked during busy practice. Serious complications can result from trace element deficiencies and toxicities, and this is especially problematic during times of product shortages. Practical information on parenteral trace element use can be gleaned from case reports, some retrospective studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 54 publications
0
4
0
4
Order By: Relevance
“…Zn 2þ and Cu 2þ [44,45]), while trivalent metals, whose affinity for InsP 6 is very much higher than divalents [46] and which are essential dietary components (e.g. Cr 3þ [47]), have not been studied in this context. Overall, this leads us to the conclusion that chronically altering cation absorption from the gut by artificially loading the diet with a non-specific chelator [39] in the hope that it might impact indirectly on cancer or other pathologies seems highly inadvisable.…”
Section: Discussionmentioning
confidence: 99%
“…Zn 2þ and Cu 2þ [44,45]), while trivalent metals, whose affinity for InsP 6 is very much higher than divalents [46] and which are essential dietary components (e.g. Cr 3þ [47]), have not been studied in this context. Overall, this leads us to the conclusion that chronically altering cation absorption from the gut by artificially loading the diet with a non-specific chelator [39] in the hope that it might impact indirectly on cancer or other pathologies seems highly inadvisable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, positive results in those trials cannot be clearly attributed solely to Se supplementation. Notwithstanding this, according to the concept of nutrient replacement, by which micronutrient substitution is aimed at replenishing losses and target restoration of physiological function [60], Se must be supplemented at standard doses by the enteral (77–100 μg/day) or the parenteral (100–400 μg/day) route [61] because the results of our meta-analysis do not refute previously recommended Se substitution doses.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium functions via proteins known as selenoproteins [39,40]. The most important selenoprotein is glutathione peroxidase (GSH-Px), which assists the body in defending against oxidative stress by reducing cell membrane damage from lipid hydroperoxides and hydrogen peroxide.…”
Section: Trace Elementsmentioning
confidence: 99%
“…Past recommendations for dosages have fluctuated, but the most recent recommendation from A.S.P.E.N. is 60–100 mcg/day for PN trace element formulations [3,39,43]. Btaiche et al [17] found in their review of HPN patients that a dose of 70 mcg/day, which was above the A.S.P.E.N.…”
Section: Trace Elementsmentioning
confidence: 99%